2018
DOI: 10.24188/recia.v10.n2.2018.620
|View full text |Cite
|
Sign up to set email alerts
|

Aprovechamiento tradicional de mamíferos silvestres en Pitzotlan, Morelos, México

Abstract: Se analiza el conocimiento etnozoológico que conservan los habitantes de Pitzotlán, relativo a los mamíferos silvestres. Mediante técnicas etnozoológicas se registró el aprovechamiento de 6 órdenes, 11 familias y 20 especies, de las cuales el 55% de las especies tienen los siguientes valores de uso: alimentario (100%), medicinal (45%), animales de compañía (18%), ornamental (18%), amuleto (18%) y en la fabricación de herramientas (9%). Su explotación se lleva a cabo mediante la cacería de subsistencia, en este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
2
6
0
4
Order By: Relevance
“…Figure 3 shows the importance of each registered use value for the wild vertebrates; the alimentary (0.54), medicinal (0.46) and ornamental (0.43) uses stand out. The use values registered in this study have been reported too for other communities in Mexico (Estrada et al 2018;García et al 2018;Velarde & Cruz 2015), being salient the use value as foodstuff in Mesoamerica (Guerra et al 2010), Colombia (Londono, 2009), Argentina (Cruz & Courtalon 2017) and Peru (Vela et al 2017) just as we report for the community under study. Besides, the use of fauna species as foodstuff and as a resource in traditional medicine is a common practice in different parts of Latin America; particularly in rural communities, wild animals provide meat for the diet and an accessible and socio-culturally acceptable alternative for the treatment of diverse ailments Machado et al 2016).…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Figure 3 shows the importance of each registered use value for the wild vertebrates; the alimentary (0.54), medicinal (0.46) and ornamental (0.43) uses stand out. The use values registered in this study have been reported too for other communities in Mexico (Estrada et al 2018;García et al 2018;Velarde & Cruz 2015), being salient the use value as foodstuff in Mesoamerica (Guerra et al 2010), Colombia (Londono, 2009), Argentina (Cruz & Courtalon 2017) and Peru (Vela et al 2017) just as we report for the community under study. Besides, the use of fauna species as foodstuff and as a resource in traditional medicine is a common practice in different parts of Latin America; particularly in rural communities, wild animals provide meat for the diet and an accessible and socio-culturally acceptable alternative for the treatment of diverse ailments Machado et al 2016).…”
Section: Resultssupporting
confidence: 83%
“…Multiple use of wild fauna.-We registered 14 species of vertebrates with multiple use value (Figure 5), among them being salient the whitetail deer Odocoileus virginianus, the rattlesnake Crotalus culminatus and the black iguana Ctenosaura pectinata, that register four use values each; these species have been also reported with multiple use values by Cortés et al (2013) in Sinaloa and Reyna et al (2015) and García et al (2018) in Morelos, México.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations